2019
DOI: 10.1073/pnas.1903844116
|View full text |Cite
|
Sign up to set email alerts
|

Postreproductive killer whale grandmothers improve the survival of their grandoffspring

Abstract: Understanding why females of some mammalian species cease ovulation prior to the end of life is a long-standing interdisciplinary and evolutionary challenge. In humans and some species of toothed whales, females can live for decades after stopping reproduction. This unusual life history trait is thought to have evolved, in part, due to the inclusive fitness benefits that postreproductive females gain by helping kin. In humans, grandmothers gain inclusive fitness benefits by increasing their number of surviving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 34 publications
0
59
0
Order By: Relevance
“…Inclusive fitness also underpins evolutionary explanations for a rare phenomenon in nature: menopause, which has only been recorded as prevalent in a few vertebrate species that includes humans and four toothed whale species (including beluga whales) 60 62 . New research on killer whales, for example, found that assistance provided by post-reproductive grandmothers improved the survival of their grandoffspring 63 . Some of these matrilineal whales may form matriarchal societies where older females have substantial influence over kin as seen in other, long-lived matrilineal species including African elephants ( Loxodonta africana ) 61 , 64 66 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusive fitness also underpins evolutionary explanations for a rare phenomenon in nature: menopause, which has only been recorded as prevalent in a few vertebrate species that includes humans and four toothed whale species (including beluga whales) 60 62 . New research on killer whales, for example, found that assistance provided by post-reproductive grandmothers improved the survival of their grandoffspring 63 . Some of these matrilineal whales may form matriarchal societies where older females have substantial influence over kin as seen in other, long-lived matrilineal species including African elephants ( Loxodonta africana ) 61 , 64 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Inclusive fitness benefits alone seem insufficient explanations for the evolution of group living in beluga whales. The frequency with which adult female belugas associate, and presumably cooperate, with non-kin also complicates studies of menopause where contributing to the fitness of kin (along with a long lifespan) is considered the basis for its evolution 61 , 63 , 69 , 70 . Our findings indicate that evolutionary explanations for group living and cooperation in beluga whales must expand beyond strict inclusive fitness arguments to include other evolutionary mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual differences in survival translate to dissimilarities in estimated maximum ages of ENP southern residents between females (80-90 years) and males (50-60 years). This increased post-reproductive lifespan of resident females is beneficial to inclusive fitness through increasing the survival of their grandoffspring and through the transfer of ecological knowledge (Foster et al 2012, Brent et al 2015, Croft et al 2017, Nattrass et al 2020. The apparent absence of sex differences in survival for the Marion Island population may be due to an incomplete dataset where most calves and juveniles…”
Section: Global Comparisonmentioning
confidence: 99%
“…Globally, the demography of killer whales has been best studied in the coastal waters of British Columbia and Washington State in the ENP and in the Gulf of Alaska (Bigg et al 1990, Olesiuk et al 1990, Brault and Caswell 1993, Foster et al 2012, Matkin et al 2012, DFO 2019, Towers et al 2019, Nattrass et al 2020. It is from these long-term longitudinal studies that most of our understanding of killer whale life-history and demography arises, such as age-and sex-specific survival rates.…”
mentioning
confidence: 99%
“…When it comes to the post-reproductive aging phenomenon in humans, the most plausible explanation includes benefits that post-reproductive females can provide by assisting their relatives (so-called grandmother hypothesis) [236]. Interestingly, a similar situation has been described in the case of killer whales in which grandmothers experiencing the post-reproductive period of life increased the survival of their grandoffspring [235]. Another evolutionary determinant of long post-reproductive life in killer whales may be the fact that a high ratio of females (relative to natural populations of most species) live to advanced age, therefore boosting selection on late-life effects [237].…”
Section: Killer Whale As An Example Of Post-reproductive Agingmentioning
confidence: 93%